CXCR4 Blockade Attenuates Hyperoxia Induced Lung Injury in Neonatal Rats - Drummond, Shelley (Neonatology, 2015)
BACKGROUND: Lung inflammation is a key factor in the pathogenesis of bronchopulmonary dysplasia (BPD). Stromal derived factor-1 (SDF-1) and its receptor chemokine receptor 4 (CXCR4) modulate the inflammatory response. Whether antagonism of CXCR4 will alleviate lung inflammation in neonatal hyperoxia-induced lung injury is unknown. OBJECTIVE: To determine whether CXCR4 antagonism would attenuate lung injury in rodents with experimental BPD by decreasing pulmonary inflammation. METHODS: Newborn rats exposed to normoxia (RA) or hyperoxia (FiO(2)=0.9) from postnatal day 2 (P2)-P16 were randomized to receive the CXCR4 antagonist, AMD3100 or placebo (PL) from P5 to P15. Lung alveolarization, angiogenesis, and inflammation were evaluated at P16. RESULTS: As compared to RA, hyperoxic-PL pups had a decrease in alveolarization, reduced lung vascular density and increased lung inflammation. In contrast, AMD3100-treated hyperoxic pups had improved alveolarization and increased angiogenesis. This improvement in lung structure was accompanied by a decrease in bronchoalveolar lavage fluid macrophage and neutrophil count and reduced lung myeloperoxidase activity. CONCLUSION: CXCR4 antagonism decreases lung inflammation and improves alveolar as well as vascular structure in neonatal rats with experimental BPD. These findings suggest a novel therapeutic strategy to alleviate lung injury in preterm infants with BPD.